Gas Chromatography-Mass Spectrometry Analysis and Antidiabetic Effect of Fractionated Extract of Strophanthus hispidus - Muyiwa SAMUEL FAGEYINBO; Temitayo ESTHER ADEYEOLUWA; Abidemi JAMES AKINDELE; Esther OLUWATOYIN AGBAJE (African Journal of Pharmacy and Alternative Medicine, 2026)
Strophanthus hispidus DC (Apocynaceae) is a valued African plant that has been used as a remedy of various disease conditions. This study identified compounds present using GC-MS as well as the potential antidiabetic effects of the n-butanol, ethyl acetate, and aqueous fractions. Gas Chromatography Mass Spectrometry (GC-MS) was carried out using the Agilent 7890 A GC with a J&W HP-5MS column (30 m x 0.320 mm i.d. x 0.25 μm). The effects of the fractions (100 mg/kg each) on blood glucose levels, body weight, biochemical parameters, lipid profile, serum insulin, hepatic glycogen, and haemoglobin levels were evaluated in alloxan-induced hyperglycaemic rats. The GC-MS analysis revealed the presence of Decanoic acid methyl ester; methyl 15-acetoxy hexadecanoate; Hydrazine propyl; and Cyclobut-1-enyl methanol. A significant (p